Preparation and Characterization of Small-Size and Strong Antioxidant Nanocarriers to Enhance the Stability and Bioactivity of Curcumin - Shanshan Tie; Yujin Yang; Jiawei Ding; Yanyan Li; Mengmeng Xue; Jianrui Sun; Fang Li; Qiuxia Fan; Ying Wu; Shaobin Gu (Foods)
The purpose of this study was to design nanocarriers with small-size and antioxidant properties for the effective encapsulation of curcumin. Here, procyanidins, vanillin, and amino acids were used to successfully prepare nanocarriers of a controllable size in the range of 328~953 nm and to endow antioxidant ability based on a one-step self-assembly method. The reaction involved a Mannich reaction on the phenolic hydroxyl groups of procyanidins, aldehyde groups of vanillin, and amino groups of amino acids. Subsequently, curcumin nanoparticles were prepared by loading curcumin with this nanocarrier, and the encapsulation efficiency of curcumin was 85.97%. Compared with free curcumin, the antioxidant capacity and photothermal stability of the embedded curcumin were significantly improved, and it could be slowly released into simulated digestive fluid. Moreover, using the corticosterone-induced PC12 cell injury model, the cell viability increased by 23.77% after the intervention of curcumin nanoparticles, and the cellular antioxidant capacity was also significantly improved. The nanoparticles prepared in this work can effectively improve the solubility, stability, and bioactivity of curcumin, which provides a reference for the embedding and delivery of other hydrophobic bioactive compounds.